2012
DOI: 10.1016/j.febslet.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into the interaction of ADP‐ribose with the PARP WWE domains

Abstract: a b s t r a c tThe WWE domain is often identified in proteins associated with ubiquitination or poly-ADP-ribosylation. Structural information about WWE domains has been obtained for the ubiquitination-related proteins, such as Deltex and RNF146, but not yet for the poly-ADP-ribose polymerases (PARPs). Here we determined the solution structures of the WWE domains from PARP11 and PARP14, and compared them with that of the RNF146 WWE domain. NMR perturbation experiments revealed the specific differences in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 23 publications
0
47
0
Order By: Relevance
“…However, to complete our understanding of why certain macrodomains recognize PARylated and others MARylated substrates, or in fact whether certain macrodomains preferentially recognize only certain MARylated residues, the structures of a macrodomain with ADP-ribosylated acceptor peptides are needed . In addition, it would be interesting to understand how the two ADP-ribose binding modules, macrodomains and the WWE domain of PARP14 (which has been shown not to bind ADP-ribose), as well as the MARylating activity of PARP14 all cooperate together in modifying and recognizing potential interaction partners (He et al, 2012). The CCCH PARPs PARPs 7, 12, and 13 contain a CCCH type of Zinc finger domain, which has been implicated in RNA binding (Guo et al, 2004).…”
Section: The Macro Parpsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to complete our understanding of why certain macrodomains recognize PARylated and others MARylated substrates, or in fact whether certain macrodomains preferentially recognize only certain MARylated residues, the structures of a macrodomain with ADP-ribosylated acceptor peptides are needed . In addition, it would be interesting to understand how the two ADP-ribose binding modules, macrodomains and the WWE domain of PARP14 (which has been shown not to bind ADP-ribose), as well as the MARylating activity of PARP14 all cooperate together in modifying and recognizing potential interaction partners (He et al, 2012). The CCCH PARPs PARPs 7, 12, and 13 contain a CCCH type of Zinc finger domain, which has been implicated in RNA binding (Guo et al, 2004).…”
Section: The Macro Parpsmentioning
confidence: 99%
“…Although very little is known about PARPs 6, 8, and 11, a recent study of the WWE domain present in PARP11 shows that it preferentially binds the terminal ADP-ribose groups instead of PAR. Such binding specificity to different ADP-ribose metabolites could be explained by the presence of an additional loop in its WWE domain (He et al, 2012). Protein ADP-Ribosylation Reversal Both PAR and MAR modifications get turned over by the timely action of ADP-ribosyl hydrolases.…”
Section: Unclassified Parpsmentioning
confidence: 99%
“…Recent studies demonstrated that the WWE domain in PARP11 is capable of binding ADP-ribose, and five amino acids within the WWE domain were identified as essential for this physical interaction in vitro [29]. We introduced point mutations to change all of these amino acid residues to alanine (A) in PARP11 to investigate a possible involvement of ADPribose binding in the subcellular localization of PARP11 (Fig.…”
Section: Parp11 Is a Mono(adp-ribosyl) Transferase That Localizes To mentioning
confidence: 99%
“…PARP11 nuclear envelope localization requires WWE domain amino acids (Y77, Q86, and R95) known to participate in ADP-ribose binding. A) Amino acids Y31, F41, Y77, Q86, and R95 in the WWE domain of PARP11 are involved in the binding to ADP-ribose [29]. To investigate the relevance of those amino acids for PARP11 subcellular localization, they were replaced with alanine (A) in expression vectors encoding the EGFP-PARP11 fusion protein.…”
Section: Sperm From Parp11 à/à Mice Have Abnormally Shaped Nucleimentioning
confidence: 99%
See 1 more Smart Citation